Net forces during tethered simulation of underwater streamlined gliding and kicking techniques of the freestyle turn - Lyttle, A. D.; Blanksby, B. A.; Elliott, B. C.; Lloyd, D. G. (Journal of Sports Sciences, 2000)
Weassessed the net forces created when towing swimmers while gliding and kicking underwater to establish an appropriate speed for initiating underwater kicking, and the most effective gliding position and kicking technique to be applied after a turn. Sixteen experienced male swimmers of similar body shape were towed by a motorized winch and pulley system. A load cell measured net force (propulsive force - drag force) at speeds of 1.6, 1.9, 2.2, 2.5 and 3.1 m·s-1. At each speed, the swimmers performed a prone streamline glide, a lateral streamline glide, a prone freestyle kick, a prone dolphin kick and a lateral dolphin kick. A two-way repeated-measures analysis of variance revealed significant differences between the gliding and kicking conditions at different speeds. The results demonstrated an optimal range of speeds (1.9 to 2.2 m·s-1) at which to begin underwater kicking to prevent energy loss from excessive active drag. No significant differences were found between the prone and lateral streamline glide positions or between the three underwater kicking techniques. Therefore, there appears to be no significant advantage in using one streamlining technique over another or in using one kicking style over another.